Investigating Women’s Language Features Used by Megawati Soekarno Putri - Ramadhani, Sri; Isnaini, Nurul Asiah; Dewi, Ratna Sari (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The study deals with women’s language features used by Megawati Soekarno Putri at BPIP National Seminar: Kick-Off Pancasila dalam Tindakan. The aims of the research are to categorize the types of women’s language features used by Megawati Soekarno Putri and analyze the realization of women’s language features in Megawati Soekarno Putri’s speech. This research was conducted by using descriptive qualitative research. The source of data was taken from script videos of Megawati Soekarno Putri’s speech at BPIP National Seminar on YouTube through BKKBN OFFICIAL Channel. The data is collected through downloading, watching, transcribing underlining and classifying the data. The data is analyzed by using interactive model proposed by Miles et.al., (2014). The findings showed that not all types of women’s language features were used by Megawati Soekarno Putri in speech at BPIP National Seminar. There were 234 utterances from nine types of women’s language features that occur in Megawati Soekarno Putri’s speech, they were 84 lexical hedges or fillers, 83 rising intonations on declarative, 13 intensifiers, 2 emphatic stress, 17 tag questions, 4 empty adjectives, 1 avoidance of strong swear words, 7 hypercorrect grammar, and 23 superpolite forms. The words found in Megawati Soekarno Putri's speech that related to the women's language features are mmm, uhh, ah, hmm, kayak/seperti (like), saya pikir/menurut saya (I think), and kayaknya/mungkin (maybe) for Lexical Hedges or fillers. ya?(right) And kan?(isn’t it) for tag question. Keren (cool), indahnya(wonderful), and cantik(beautiful) for empty adjectives. Banget, sekali (so) and banyak (very) for intensifiers. Memang, mengapa, bagaimana for hypercorrect grammar. Tolong(please), maaf(sorry), dengan hormat, beliau and madam for superpolite forms. Ya Allah for avoidance of strong swear words. Luar biasa! and sangat-sangat for emphatic stress.